Analisis Faktor Risiko Penyakit Tidak Menular di Kelurahan Prapatan, Kota Balikpapan, Kalimantan Timur Tahun 2023 - Tien Fatimatuzzahra; Ratih Wirapuspita Wisnuwardani; Ike Anggraeni Gunawan (Universitas Pahlawan Tuanku Tambusai, 2025)
Non-Communicable Diseases (NCDs) are a major public health challenge. The incidence of NCDs is influenced by modifiable and non-modifiable risk factors. This study aimed to evaluate the prevalence and associations of NCD risk factors in the Prapatan area through the PRAPATAN POSTER innovation. A retrospective cross-sectional study was conducted using data from 363 screenings; the prevalence of hypertension was 19.3%, diabetes 7.7%, with 51.2% being overweight or obese, 48.25% reporting physical inactivity, and 8.5% identified as smokers. Chi- square tests revealed significant associations between age and hypertension (p=0.000), age and type 2 diabetes (p=0.000), obesity and hypertension (p=0.000), as well as obesity and physical inactivity (p=0.000). Strengthening health promotion, early detection, and community- based interventions are recommended for NCD prevention and control. Keywords: Non Communicable Diseases, hypertension, diabetes, risk factors